Rizika bilančních podvodů z pohledu účetního zobrazení finančního pronájmu u nájemce - Majerová, Kateřina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Diplomová práce je zaměřena na zhodnocení rizik vzniku bilančních podvodů účetního zobrazení pronájmu u nájemce z hlediska jejich vlivu na relevantnost účetních informací a hledání řešení k jejich předcházení. V práci jsou analyzovány rozdíly mezi vykazováním finančního pronájmu podle přístupu národní účetní legislativy České republiky a podle přístupu standardu IFRS 16 – Leasingy a jejich vliv na finanční ukazatele a relevantnost účetních informací. Dále je v práci navržen postup, jehož cílem je správná kvalifikace finančního pronájmu nájemcem a postup zachycení finančního pronájmu v účetnictví nájemce, tak aby adekvátně popisoval skutečnost a ovlivňoval finanční ukazatele.

The thesis focuses on assessing the risks of balance sheet fraud in the accounting presentation of leases by the lessee in terms of their impact on the relevance of accounting information and finding solutions to prevent them. The thesis analyzes the differences between reporting financial leases according to the approach of the National Accounting Legislation of the Czech Republic and according to the approach of the IFRS 16 standard - Leases and their impact on financial indicators and the relevance of accounting information. Furthermore, the thesis proposes a procedure aimed at the correct qualification of financial leases by the lessee and the procedure for recording financial leases in the lessee's accounting, so that it adequately describes the reality and influences financial indicators.
Risks of fraudulent financial statements arising from the leasee´s recognition of financial leases
Keywords: Bilanční podvod; účetní informace; finanční pronájem; IFRS 16; Accounting fraud; accounting information; financial lease; IFRS 16